Sky-luminance distribution in Beijing. (May 2015) - Luo, T; Yan, D; Lin, R; Zhao, J
Sky-luminance distribution is the basic requirement for daylighting calculations and design. It is also important for describing and defining the different sky types. However, owing to the lack of test equipment and measurement data, research on sky-luminance distribution in China has been limited. Therefore, for the first time, we have obtained the sky-luminance distribution data using our self-developed spectrum sky scanner from observations over 12 months. Furthermore, we have established a relationship between the actual sky types of Beijing and the Commission Internationale de l'Eclairage standard sky model. These data are very important in the study of the daylight climate of China.